ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS BERINFAQ : STUDI KASUS ANGGOTA INFAQ DA’WAH CLUB DEWAN DA'WAH ISLAMIYAH INDONESIA PROVINSI JAWA TENGAH KANTOR SURAKARTA - AGUS SAMSONO (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2018)
Objective: This research aims to analyze what factors influence the loyalty of giving infaq members Infaq Da'wah Club and what factors are most dominant among these factors. Methodes: The methodology used in this research is quantitative approach with method. In this research there is one dependent Variable (Variable Y) and 3 Variable Free (Variebel X). Variable Y is Loyalty, Variable X1 Program, Variable X2 Service and Variebel X3 Reporting. Results: Results of Multiple Linear Regression Analysis shows Variable X1 (Program Work) has a score of 0.464 to variable Y (Loyalty), Variable X2 (Services) has a score of 0.484 to variable Y (loyalty) and Variable X3 (Reporting) has a score of 0.477 to variable Y (loyalty). This shows the work program, service and reporting done by the manager of Infaq Da'wah Club. Being loyal to give infaq member Infaq Da'wah Club. This is reinforced by result of Fasi 25.816 test which shows variable X1 (Program), X2 (Service), X3 (Reporting) significantly simultaneously to Y (Loyalty). While the t test results from each variable shows a value greater than ɑ- value (0.05) which indicates that variable has an effect on variable Y. Variable X1 with value 2,687 & gt; ɑ-value (0,05), Variable X2 (Service) with value 2,559 & gt; ɑ- value (0,05), Variable X3 (Reporting) with value 3,243 & gt; ɑ-value (0.05), all three of which are partially to variable Y (Loyalty). Thus the program of work, services and financial reports partially to loyalty gives infaq members Infaq Da'wah Club. From the T test results, showing the variable X3 (Reporting) with a value of 3.243 is a factor that loyalty gives infaq members Infaq Da'wah Club. The amount of Adjusted R2 is 0.319, indicating that 31% of loyalty in giving infaq members of the three independent variables namely Work Program, Service and Reporting, while 69% influenced other factors outside this research.